Producción científica mundial sobre la vacuna contra el Covid-19: análisis del período 2020-2021 - Arias-Chávez, Dennis (2021)
Objective. Characterize the global scientific production on the vaccine to combat Covid-19 in the Scopus, Web of Science, Google Academic, PubMed, Microsoft Academic and Crosreff databases between the months of January 2020 to April 2021. Material and methods. We worked with a universe made up of 3817 articles obtained. Bibliometric indicators were calculated through Publish or Perish v. 7.31, VOSwiever, Pubreminer, Dimensions and the same analytical software from the chosen databases. Results. The results indicate a total of 30619 citations, with an average of 5103; 11 and 2251 citations per year, citations per article and citations per author respectively. On average, publications have an h-index of 26.00, a g-index of 42.00, and an e-index of 33.59. Prompetchara’s study, Eakachai; Kettoy, Chutitorn; Palaga, Tanapat, (2020), the British Medical Journal - BMJ, USA is the main producer of scientific evidence on vaccines and the type of scientific production that stands out the most are original articles. Conclusions. These results show that the production of scientific articles on the vaccine to combat Covid-19 has experienced significant growth, which shows the enormous scientific effort made worldwide to control this disease.